PERAN PENDAFTARAN NIB DALAM LEGALITAS USAHA DAN PEMBERDAYAAN UMKM DI ALUN-ALUN CONTONG KOTA SURABAYA - Wibowo, Talitha; Sugito (Education and Talent Development Center of Indonesia, 2025)
This community service program aims to evaluate the effectiveness of Business Identification Number (NIB) registration through the Online Single Submission (OSS) system as a form of business legality for Micro, Small, and Medium Enterprises (MSMEs) in Alun-Alun Contong Village, Surabaya City. The main problems faced by MSME partners are low digital and legal literacy, as well as limited access to technological devices, so that many business actors do not yet have a NIB. The activity was carried out using a community-based participatory approach that includes the stages of initial identification, education and socialization, and direct technical assistance in the NIB registration process through OSS. The results showed that out of 18 MSME partners who were assisted, 14 partners successfully completed the NIB registration process through this assistance (77.78%). This success shows the effectiveness of a direct and communicative approach in overcoming digital and procedural barriers that have been obstacles. In addition to administrative achievements, this activity also has an impact on increasing digital literacy, business actors' self-confidence, and active involvement in the legalization process. The main conclusion of this activity is that community-based mentoring contributes to strengthening the sustainable formal MSME ecosystem. Suggestions for further development are the provision of visual-based educational media and digital communities so that MSMEs are able to carry out legalization independently.